(untitled) (Nigerian Journal of Health Sciences, 2023)
Background: Adolescence marks the beginning of transition between childhood and adulthood. However, inadequate knowledge about this transition remains a challenge among this group. Objective: This study was therefore designed to investigate the knowledge of puberty, sexually transmitted infections (STIs), and sexual behavior among very young female adolescent students aged 10-14 years in Agbor metropolis, Nigeria. Methods: A qualitative and quantitative cross‑sectional study was conducted among female adolescent students(10–14 years). The discussants were grouped into ages 10–12 years and 13–14 years. A total of four focus group discussions were conducted among the two groups in two government secondary schools in the study area, while a semi‑structured questionnaire which comprised sociodemographic characteristics, knowledge of puberty, STIs, and sexual behavior was used to collect the quantitative data. The qualitative data were analyzed thematically for themes and content, while the quantitative data were analyzed using SPSS Version 15.0. Results: The result shows most of the respondents 96 (97.0%) have heard of puberty and were able to define puberty 82 (85.40%). Furthermore, majority of the respondents have heard of the word human immunodeficiency virus 95 (96.0%) and STI 60 (60.6%), but few 4 (4.0%) have heard of the word contraceptive. In addition, only 12 (12.10%) of the respondents have a boyfriend, out of which only 3 (3.0%) have had sex at the age of 9 and 11 years, respectively. Conclusions: The results shows some of the respondents are already sexually active at that young age, therefore more intervention programs targeting these group of students should be carried out regularly in schools nationwide.